2018
DOI: 10.2147/ijn.s151474
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of Huperzine A to the brain using lactoferrin-conjugated N-trimethylated chitosan surface-modified PLGA nanoparticles for treatment of Alzheimer’s disease

Abstract: Background Safe and effective delivery of therapeutic drugs to the brain is important for successful therapy of Alzheimer’s disease (AD). Purpose To develop Huperzine A (HupA)-loaded, mucoadhesive and targeted polylactide-co-glycoside (PLGA) nanoparticles (NPs) with surface modification by lactoferrin (Lf)-conjugated N-trimethylated chitosan (TMC) (HupA Lf-TMC NPs) for efficient intranasal delivery of HupA to the brain for AD treatment. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(109 citation statements)
references
References 44 publications
1
101
0
Order By: Relevance
“…Another study developed huperzine A-loaded, mucoadhesive, and targeted PLGA nanoparticles with surface modification by lactoferrin-conjugated N-trimethylated chitosan for efficient intranasal delivery of huperzine A to the brain for AD treatment. These nanoparticles showed good sustained-release effect, adhesion, targeting ability, and a broad application prospect as a nasal drug delivery carrier [207]. These studies suggest that particle transport via the nose-to-brain route is highly affected by the particle surface chemistry.…”
Section: Nanoparticles Composed Of Chitosan and Chitosan Derivativesmentioning
confidence: 83%
“…Another study developed huperzine A-loaded, mucoadhesive, and targeted PLGA nanoparticles with surface modification by lactoferrin-conjugated N-trimethylated chitosan for efficient intranasal delivery of huperzine A to the brain for AD treatment. These nanoparticles showed good sustained-release effect, adhesion, targeting ability, and a broad application prospect as a nasal drug delivery carrier [207]. These studies suggest that particle transport via the nose-to-brain route is highly affected by the particle surface chemistry.…”
Section: Nanoparticles Composed Of Chitosan and Chitosan Derivativesmentioning
confidence: 83%
“…Non-invasive administration routes remain preferable in humans and among them, although bearing some limitations, oral management represents a safe and practical approach for Lf supplementation. Beside oral administration [48], several different other modes have been tested in animal models and humans, including aerosolized [45,46], intranasal [52], sublingual [53], intravenous [54], intraperitoneal [55], and intravaginal administration [56].…”
Section: Lactoferrin Bioavailability: Absorption and Body Deliverymentioning
confidence: 99%
“…Furthermore, cellular uptake experiments demonstrated that accumulation of Lf-TMC NPs was higher than nontargeted analogs in SH-SY5Y and 16HBE cells. HupA-PLGA-NPs improved the bioavailability and targeting ability of the drug (Meng et al, 2018). In AD rat model, berberine (BRB)-loaded multiwalled carbon nanotubes (MWCNTs) coated with phospholipid and polysorbate, remanded the memory impairment and reduced the β-amyloid induced-AD compared with its free form (Lohan et al, 2017).…”
Section: Plant-mediated Nano Systemsmentioning
confidence: 99%